The Politics of Memory as "the Art of Light Touches" - O. V. Gaman-Golutvina (Сравнительная политика, 2024)
The main topic of this issue is the phenomenon and politics of historical memory. At the end of the 20th century, the concept of historical memory emerged in the subject field of socio-humanitarian knowledge along with the notions of historical knowledge, historical consciousness and perceptions of the past as a tool for re-interpreting the relationship between history, memory and identity. The relevant research is often defined as "turn", "memorial paradigm", "memorial revolution" and even "memorial boom". The German researcher A. Assmann even used the term "popular fascination" with the study of images of the past as interpretive models for re-interpreting the present. The memorial paradigm adopted the ideas of the French sociologist Maurice Halbwachs, the author of Collective Memory, who died in a Nazi concentration camp, and, above all, Halbwachs' key idea: if history as a science strives for universality, and with all the divisions into national histories or histories by periods, there is only one history, then there are simultaneously several variants of collective memory.